1992
DOI: 10.1007/bf00867593
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans' cell histiocytosis and the nervous system

Abstract: We report two cases of Langerhans' cell histiocytosis with unusual central nervous system (CNS) involvement. The first patient had behavioural disturbances, memory loss and diabetes insipidus. His response to a range of treatments was poor. The second patient presented with seizures and headaches suggestive of raised intracranial pressure. Etoposide (VP16) chemotherapy led to a dramatic clinical and radiological improvement. The various CNS manifestations of Langerhans' cell histiocytosis and their management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The slow processing speed observed for JK, and to a lesser extent for AB, is also consistent with observations of other LCH patients [13]. Difficulties with short-term memory, formally assessed here, have been described by others, who have found that these difficulties did not resolve even when treatment seemed to be effective in other domains [14]. These difficulties will almost certainly impact the LCH child's ability to learn new material as well as to demonstrate knowledge and ability when assessed.…”
Section: Discussionsupporting
confidence: 91%
“…The slow processing speed observed for JK, and to a lesser extent for AB, is also consistent with observations of other LCH patients [13]. Difficulties with short-term memory, formally assessed here, have been described by others, who have found that these difficulties did not resolve even when treatment seemed to be effective in other domains [14]. These difficulties will almost certainly impact the LCH child's ability to learn new material as well as to demonstrate knowledge and ability when assessed.…”
Section: Discussionsupporting
confidence: 91%
“…Progressive neurologic abnormalities, such as subtle cerebellar ataxia and nystagmus, also have been shown to precede clinical diabetes insipidus by many years. [25][26][27] Similarly, pulmonary symptoms and spontaneous pneumothorax most likely are late symptoms that reflect more advanced disease. 21,28 Pulmonary LCH generally displays an insidious and often progressive natural history that makes determination of its time of onset very difficult.…”
Section: Natural History Of the Diseasementioning
confidence: 99%
“…The most prominent abnormality was an abnormal eating pattern and obesity; fi ve patients developed morbid obesity, which was diffi cult to control 6 . Further abnormalities, such as disturbances in thermoregulation and adipsia, can make DI diffi cult to treat and complicate the overall management of these problematic cases 14 . No such abnormalities were noted in our subject.…”
Section: Histiocytosis: An Uncommon Presentation With Hypopituitarismmentioning
confidence: 99%